Manufacturing method of insulation material
The described method for manufacturing heat insulating materials using airgel particles and a water-soluble polymer under controlled pressure effectively prevents resin penetration and ensures uniform dispersion, resulting in improved insulation and film strength.
Patent Information
- Application Number
- JP2021574703
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Existing methods for producing heat insulating materials with airgel particles result in resin penetration into airgel pores, leading to deteriorated insulation properties and insufficient film strength due to resin component penetration and uneven distribution.
A method involving the application of a coating liquid with airgel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium under pressure to aggregate airgel particles, followed by removing a portion of the liquid medium, thereby reducing resin penetration and ensuring uniform dispersion.
The method produces a heat insulating material with high insulation properties and film formability by suppressing resin penetration into airgel pores and preventing cracking.
Smart Images

Figure 0007616080000001 
Figure 0007616080000002 
Figure 0007616080000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for manufacturing a thermal insulating material. [Background technology]
[0002] Aerogel is known as a material with excellent thermal insulation properties. Furthermore, methods have been proposed in which aerogel is processed into particles and used as a constituent material for thermal insulation (e.g., Patent Documents 1 and 2). Patent Document 1 proposes using particulate aerogel as a filler between resin plates that constitute thermal insulation windows. Patent Document 2 discloses a method for producing a thermal insulation material (molded body) by preparing an aqueous dispersion containing aerogel particles and organic fibers, and then evaporating the water to obtain an intermediate product, which is then press-molded. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2012-91943 [Patent Document 2] Japanese Patent Application Laid-Open No. 2014-35044 Summary of the Invention [Problem to be solved by the invention]
[0004] Composite materials in which aerogel particles are dispersed in a resin component are expected to have excellent heat resistance. However, when such composite materials are made into coatings, there are issues such as the resin component penetrating into the pores of the aerogel particles, causing the pore structure to be lost and resulting in a decrease in heat insulation, and the coating film not being strong enough and prone to cracking.
[0005] Therefore, an object of the present invention is to provide a method for producing a heat insulating material that can suppress the penetration of resin components into the pores of aerogel particles and can produce a heat insulating material that has high heat insulating properties and high film-forming properties. [Means for solving the problem]
[0006] One aspect of the present invention relates to a method for producing a thermal insulating material, including: a coating step of mixing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium so that the aerogel particles aggregate, and applying the resulting coating liquid using a coating means that applies a pressure of 1.5 MPa or less to the coating liquid to obtain a coating film; and a removal step of removing at least a portion of the liquid medium from the coating film to obtain a thermal insulating material.
[0007] In the coating liquid used in the above manufacturing method, the aerogel particles aggregate, reducing the contact interface between the aerogel particles and the resin component, thereby suppressing penetration of the resin component into the pores of the aerogel particles. Furthermore, the coating liquid is not a mixture of pre-prepared aerogel particle aggregates, but rather is formed by agglomerating the aerogel particles during mixing with other components. Therefore, the aerogel particles and their aggregates are uniformly dispersed, preventing uneven coating film and cracking due to uneven distribution of the aerogel particles. Furthermore, the manufacturing method uses a water-soluble polymer with hydrophobic groups as the resin component, further improving the dispersibility of the aerogel particles. Even when the aerogel particle filling rate is high, the aerogel particles and their aggregates are uniformly dispersed in the coating liquid. Furthermore, the manufacturing method uses a coating means that applies a pressure of 1.5 MPa or less to the coating liquid, thereby suppressing the breakup of aggregates due to the load during application. Therefore, the manufacturing method produces a thermal insulation material with high thermal insulation properties and excellent film-forming properties.
[0008] In one embodiment, the coating liquid contains aggregates of the aerogel particles, and the average diameter of the aggregates may be 2 to 40 times the average diameter of the aerogel particles. The coating liquid containing such aggregates exhibits the above-mentioned effects more significantly.
[0009] In one embodiment, when the diluted solution obtained by diluting the coating liquid is observed under an optical microscope, the area occupied by the aerogel particles and aerogel particle aggregates within the observation field may be 50% or more, thereby more significantly achieving the above-mentioned effects.
[0010] In one embodiment, the total content of the aerogel particles and the aerogel particle aggregates in the coating liquid may be 70% by volume or more based on the total volume of the solid content.
[0011] In one embodiment, the water-soluble polymer may include a cellulose-based resin.
[0012] In one embodiment, the pore volume of the insulating material is 0.15 g / cm 3 It may be more than that. [Effects of the Invention]
[0013] According to the present invention, there is provided a method for producing a heat insulating material, which can suppress the penetration of a resin component into the pores of aerogel particles and can produce a heat insulating material having high heat insulating properties and high film-forming properties. DETAILED DESCRIPTION OF THE INVENTION
[0014] Preferred embodiments of the present invention will be described in detail below. However, the present invention is not limited to the following embodiments. In this specification, a numerical range indicated using "to" indicates a range that includes the numerical values before and after "to" as the minimum and maximum values, respectively. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this embodiment can be used alone or in combination of two or more.
[0015] The method for producing a heat insulating material according to this embodiment includes a coating step in which a coating liquid obtained by mixing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium so as to cause the aerogel particles to aggregate is applied to the coating liquid by a coating means that applies a pressure of 1.5 MPa or less to the coating liquid to obtain a coating film, and a removal step in which at least a portion of the liquid medium is removed from the coating film to obtain a heat insulating material.
[0016] In the coating liquid used in this embodiment, the aerogel particle aggregation reduces the contact interface between the aerogel particles and the resin component, thereby suppressing penetration of the resin component into the pores of the aerogel particles. Furthermore, the coating liquid is not a mixture of aerogel particle aggregates prepared in advance, but rather is formed by agglomerating the aerogel particles during mixing with other components. Therefore, the aerogel particles and their aggregates are uniformly dispersed, preventing uneven coating film and cracking due to uneven distribution of the aerogel particles. Furthermore, the use of a water-soluble polymer with hydrophobic groups as the resin component in this manufacturing method further improves the dispersibility of the aerogel particles, ensuring uniform dispersion of the aerogel particles and their aggregates in the coating liquid even when the aerogel particle filling rate is high. Furthermore, the manufacturing method uses a coating means with a pressure of 1.5 MPa or less applied to the coating liquid, thereby suppressing the breakup of aggregates due to the load during application. Therefore, this manufacturing method allows for the production of a thermal insulating material with high thermal insulation and excellent film-forming properties.
[0017] <Aerogel> In a narrow sense, a dry gel obtained by supercritical drying of a wet gel is called an aerogel, a dry gel obtained by drying under atmospheric pressure is called a xerogel, and a dry gel obtained by freeze-drying is called a cryogel. However, in this embodiment, a low-density dry gel obtained from a wet gel regardless of these drying methods is called an "aerogel." That is, in this embodiment, "aerogel" refers to a "gel comprised of a microporous solid in which the dispersed phase is a gas," which is an aerogel in the broad sense. Generally, the interior of an aerogel has a mesh-like microstructure and a cluster structure in which particulate aerogel components of approximately 2 to 20 nm are bonded. Between the skeletons formed by these clusters, there are pores of less than 100 nm. This gives the aerogel a three-dimensional microporous structure.
[0018] The aerogel according to this embodiment is, for example, a silica aerogel containing silica as a main component. Examples of the silica aerogel include so-called organic-inorganic hybrid silica aerogels into which an organic group (such as a methyl group) or an organic chain has been introduced.
[0019] Examples of the aerogel according to this embodiment include the following aspects. By employing these aspects, it is easy to obtain an aerogel that is excellent in heat insulation, flame retardancy, heat resistance, and flexibility. By employing each aspect, it is possible to obtain an aerogel that has the heat insulation, flame retardancy, heat resistance, and flexibility appropriate for each aspect.
[0020] (First aspect) The aerogel according to this embodiment may have a structure represented by the following general formula (1): The aerogel according to this embodiment may have a structure represented by the following general formula (1a) as a structure including the structure represented by formula (1). [ka] [ka]
[0021] In formula (1) and formula (1a), R 1 and R 2 each independently represents an alkyl group or an aryl group, and R 3 and R 4 each independently represents an alkylene group. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. p represents an integer of 1 to 50. In formula (1a), two or more R 1 may be the same or different, and similarly, two or more R 2 In formula (1a), two R 3 may be the same or different, and similarly, two R 4may be the same or different.
[0022] By introducing the structure represented by the above formula (1) or formula (1a) into the skeleton of the aerogel as an aerogel component, a low thermal conductivity and flexible aerogel can be obtained. 1 and R 2 are each independently an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and examples of the alkyl group include a methyl group, etc. In addition, in formula (1) and formula (1a), R 3 and R 4 are each independently an alkylene group having 1 to 6 carbon atoms, and examples of the alkylene group include an ethylene group, a propylene group, etc. In formula (1a), p can be 2 to 30, and may be 5 to 20.
[0023] (Second aspect) The aerogel according to this embodiment has a ladder-type structure including struts and bridges, and the bridges may have a structure represented by the following general formula (2). By incorporating such a ladder-type structure into the skeleton of the aerogel as an aerogel component, heat resistance and mechanical strength can be improved. In this embodiment, the "ladder-type structure" refers to a structure having two struts and bridges connecting the struts (a structure having a so-called "ladder" shape). In this embodiment, the skeleton of the aerogel may have a ladder-type structure, or the aerogel may partially have a ladder-type structure. [ka]
[0024] In formula (2), R 5 and R 6are each independently an alkyl group or an aryl group, and b is an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in formula (2), when b is an integer of 2 or more, two or more R 5 may be the same or different, and similarly, two or more R 6 may be the same or different.
[0025] By introducing the above structure into the skeleton of an aerogel as an aerogel component, an aerogel having superior flexibility to, for example, aerogels having a structure derived from a conventional ladder-type silsesquioxane (i.e., a structure represented by the following general formula (X)) can be obtained. Silsesquioxanes have the composition formula: (RSiO 1.5 ) n The polysiloxane has the following general formula (X), and can have various skeletal structures such as a cage structure, a ladder structure, and a random structure. As shown in the following general formula (X), in aerogels having a structure derived from conventional ladder-type silsesquioxanes, the structure of the bridged moieties is -O-. However, in the aerogel according to this embodiment, the structure of the bridged moieties is the structure (polysiloxane structure) represented by the above general formula (2). However, the aerogel according to this embodiment may further have a structure derived from silsesquioxane in addition to the structure represented by general formula (2). [ka]
[0026] In formula (X), R represents a hydroxy group, an alkyl group, or an aryl group.
[0027] The structure that forms the support portion, its chain length, and the spacing between the structures that form the bridging portion are not particularly limited, but from the viewpoint of further improving heat resistance and mechanical strength, the ladder structure may have a ladder structure represented by the following general formula (3). [ka]
[0028] In formula (3), R 5 , R 6 , R 7 and R 8 each independently represents an alkyl group or an aryl group, a and c each independently represent an integer of 1 to 3000, and b represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in formula (3), when b is an integer of 2 or more, two or more R 5 may be the same or different, and similarly, two or more R 6 In addition, in formula (3), when a is an integer of 2 or more, two or more R 7 may be the same or different, and similarly, when c is an integer of 2 or more, two or more R 8 may be the same or different.
[0029] In order to obtain better flexibility, R 5 , R 6 , R 7 and R 8 (However, R 7 and R 8 (only in formula (3)) each independently includes an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and examples of the alkyl group include a methyl group, etc. In formula (3), a and c each independently can be 6 to 2000, but may be 10 to 1000. In formulas (2) and (3), b can be 2 to 30, but may be 5 to 20.
[0030] (Third Aspect) The aerogel according to this embodiment may be a dried wet gel (obtained by drying a wet gel produced from a sol: a dried wet gel derived from a sol) that is a condensate of a sol containing at least one selected from the group consisting of a silicon compound having a hydrolyzable functional group or a condensable functional group and a hydrolysis product of a silicon compound having a hydrolyzable functional group. The aerogel described above may also be obtained by drying a wet gel produced from a sol containing a silicon compound or the like.
[0031] A polysiloxane compound can be used as the silicon compound having a hydrolyzable functional group or a condensable functional group. That is, the sol can contain at least one compound selected from the group consisting of polysiloxane compounds having a hydrolyzable functional group or a condensable functional group and hydrolysis products of polysiloxane compounds having a hydrolyzable functional group (hereinafter sometimes referred to as "polysiloxane compound group").
[0032] The functional groups in the polysiloxane compound are not particularly limited, and may be groups that react with each other or with other functional groups. Examples of hydrolyzable functional groups include alkoxy groups. Examples of condensable functional groups include hydroxyl groups, silanol groups, carboxyl groups, and phenolic hydroxyl groups. Hydroxyl groups may be contained in hydroxyl-containing groups such as hydroxyalkyl groups. Polysiloxane compounds having hydrolyzable or condensable functional groups may further contain reactive groups (functional groups that do not fall under the category of hydrolyzable or condensable functional groups) different from the hydrolyzable or condensable functional groups. Examples of reactive groups include epoxy groups, mercapto groups, glycidoxy groups, vinyl groups, acryloyl groups, methacryloyl groups, and amino groups. Epoxy groups may be contained in epoxy-containing groups such as glycidoxy groups. Polysiloxane compounds having these functional groups and reactive groups may be used alone or in combination. Among these functional groups and reactive groups, for example, groups that improve the flexibility of the aerogel include alkoxy groups, silanol groups, and hydroxyalkyl groups. Of these, alkoxy groups and hydroxyalkyl groups can further improve the compatibility of the sol. Furthermore, from the viewpoint of improving the reactivity of the polysiloxane compound and reducing the thermal conductivity of the aerogel, the number of carbon atoms in the alkoxy groups and hydroxyalkyl groups can be 1 to 6. However, from the viewpoint of further improving the flexibility of the aerogel, the number of carbon atoms may be 2 to 5 or 2 to 4.
[0033] Examples of polysiloxane compounds having a hydroxyalkyl group in the molecule include those having a structure represented by the following general formula (A): By using a polysiloxane compound having a structure represented by the following general formula (A), the structures represented by general formula (1) and formula (1a) can be introduced into the skeleton of the aerogel. [ka]
[0034] In formula (A), R 1a represents a hydroxyalkyl group, and R2a represents an alkylene group, and R 3a and R 4a each independently represents an alkyl group or an aryl group, and n represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in formula (A), two R 1a may be the same or different, and similarly, two R 2a may be the same or different. In addition, in formula (A), two or more R 3a may be the same or different, and similarly, two or more R 4a may be the same or different.
[0035] By using a wet gel (produced from a sol) that is a condensate of a sol containing a polysiloxane compound having the above structure, it becomes easier to obtain an aerogel that has low thermal conductivity and flexibility. 1a Examples of the hydroxyalkyl group include a hydroxyethyl group and a hydroxypropyl group. 2a Examples of the alkylene group include an alkylene group having 1 to 6 carbon atoms, and examples of the alkylene group include an ethylene group and a propylene group. 3a and R 4a are each independently an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and examples of the alkyl group include a methyl group, etc. In addition, in formula (A), n can be 2 to 30, but may also be 5 to 20.
[0036] As the polysiloxane compound having a structure represented by the general formula (A), commercially available products can be used, and examples thereof include compounds such as X-22-160AS, KF-6001, KF-6002, and KF-6003 (all manufactured by Shin-Etsu Chemical Co., Ltd.), and compounds such as XF42-B0970 and Fluid OFOH 702-4% (all manufactured by Momentive).
[0037] Examples of polysiloxane compounds having alkoxy groups in the molecule include those having a structure represented by the following general formula (B): By using a polysiloxane compound having a structure represented by the following general formula (B), a ladder structure having a bridge represented by general formula (2) or (3) can be introduced into the skeleton of the aerogel. [ka]
[0038] In formula (B), R 1b represents an alkyl group, an alkoxy group, or an aryl group, and R 2b and R 3b each independently represents an alkoxy group, and R 4b and R 5b Each of R independently represents an alkyl group or an aryl group, and m represents an integer of 1 to 50. Here, examples of the aryl group include a phenyl group and a substituted phenyl group. Examples of the substituent of the substituted phenyl group include an alkyl group, a vinyl group, a mercapto group, an amino group, a nitro group, and a cyano group. In addition, in formula (B), two R 1b may be the same or different, and two R 2b may be the same or different, and similarly, two R 3b may be the same or different. In addition, in formula (B), when m is an integer of 2 or more, two or more R 4b may be the same or different, and similarly, two or more R 5b may be the same or different.
[0039] By using a wet gel (produced from a sol) that is a condensate of a sol containing the polysiloxane compound having the above structure or a hydrolysis product thereof, it becomes easier to obtain an aerogel that has low thermal conductivity and flexibility. 1bExamples of the alkyl group or alkoxy group include a methyl group, a methoxy group, and an ethoxy group. 2b and R 3b are each independently an alkoxy group having 1 to 6 carbon atoms, and examples of the alkoxy group include a methoxy group and an ethoxy group. 4b and R 5b are each independently an alkyl group having 1 to 6 carbon atoms, a phenyl group, etc., and examples of the alkyl group include a methyl group, etc. In addition, in formula (B), m can be 2 to 30, but may also be 3 to 35, or 5 to 20.
[0040] The polysiloxane compound having the structure represented by the general formula (B) can be obtained by appropriately referring to the production methods reported in JP-A Nos. 2000-26609 and 2012-233110, etc. Alternatively, XR31-B1410 (manufactured by Momentive Corporation) can also be used as the polysiloxane compound.
[0041] Since the alkoxy group is hydrolyzed, the polysiloxane compound having the alkoxy group may exist as a hydrolysis product in the sol, and the polysiloxane compound having the alkoxy group and its hydrolysis product may be mixed. Furthermore, in the polysiloxane compound having the alkoxy group, all of the alkoxy groups in the molecule may be hydrolyzed, or they may be partially hydrolyzed.
[0042] These polysiloxane compounds having a hydrolyzable functional group or a condensable functional group and hydrolysis products of polysiloxane compounds having a hydrolyzable functional group may be used alone or in combination of two or more.
[0043] When preparing the aerogel according to this embodiment, silicon compounds having hydrolyzable or condensable functional groups can be silicon compounds other than the polysiloxane compounds described above. That is, the sol containing the silicon compounds described above can contain at least one selected from the group consisting of silicon compounds (excluding polysiloxane compounds) having hydrolyzable or condensable functional groups and hydrolysis products of the silicon compounds having hydrolyzable functional groups (hereinafter sometimes referred to as "silicon compounds") in addition to or instead of the polysiloxane compounds described above. The number of silicon atoms in the silicon compound molecule can be one or two.
[0044] Silicon compounds having hydrolyzable functional groups in the molecule include, but are not limited to, alkyl silicon alkoxides. In order to improve water resistance, the number of hydrolyzable functional groups in the alkyl silicon alkoxides can be three or less. Examples of such alkyl silicon alkoxides include monoalkyl trialkoxysilanes, monoalkyl dialkoxysilanes, dialkyl dialkoxysilanes, monoalkyl monoalkoxysilanes, dialkyl monoalkoxysilanes, trialkyl monoalkoxysilanes, and the like. Specific examples include methyl trimethoxysilane, methyl dimethoxysilane, dimethyl diethoxysilane, dimethyl dimethoxysilane, ethyl trimethoxysilane, hexyl trimethoxysilane, and the like. Here, examples of the hydrolyzable functional group include alkoxy groups such as methoxy groups and ethoxy groups.
[0045] Examples of silicon compounds having a condensable functional group include, but are not limited to, silanetetraol, methylsilanetriol, dimethylsilanediol, phenylsilanetriol, phenylmethylsilanediol, diphenylsilanediol, n-propylsilanetriol, hexylsilanetriol, octylsilanetriol, decylsilanetriol, and trifluoropropylsilanetriol.
[0046] The silicon compound having a hydrolyzable functional group or a condensable functional group may further have the above-mentioned reactive group different from the hydrolyzable functional group and the condensable functional group (a functional group that does not fall under the category of a hydrolyzable functional group or a condensable functional group).
[0047] Examples of silicon compounds that have three or less hydrolyzable functional groups and have a reactive group include vinyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, and N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane.
[0048] Furthermore, examples of silicon compounds having a condensable functional group and a reactive group that can be used include vinyl silanetriol, 3-glycidoxypropyl silanetriol, 3-glycidoxypropyl methyl silanediol, 3-methacryloxypropyl silanetriol, 3-methacryloxypropyl methyl silanediol, 3-acryloxypropyl silanetriol, 3-mercaptopropyl silanetriol, 3-mercaptopropyl methyl silanediol, N-phenyl-3-aminopropyl silanetriol, and N-2-(aminoethyl)-3-aminopropyl methyl silanediol.
[0049] Furthermore, silicon compounds having three or less hydrolyzable functional groups at the molecular terminals, such as bistrimethoxysilylmethane, bistrimethoxysilylethane, bistrimethoxysilylhexane, ethyltrimethoxysilane, and vinyltrimethoxysilane, can also be used.
[0050] The silicon compounds (excluding polysiloxane compounds) having a hydrolyzable functional group or a condensable functional group, and the hydrolysis products of the silicon compounds having a hydrolyzable functional group may be used alone or in combination of two or more.
[0051] By using the above silicon compounds (excluding polysiloxane compounds), structures represented by the following general formulas (4) to (6) can be introduced into the skeleton of the aerogel. The aerogel according to this embodiment can have any one of these structures alone, or two or more of them.
[0052] [ka]
[0053] In formula (4), R 9 represents an alkyl group. Here, examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, and examples of the alkyl group include a methyl group.
[0054] [ka]
[0055] In formula (5), R 10 and R 11 and each independently represent an alkyl group. Examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, and examples of the alkyl group include a methyl group.
[0056] [ka]
[0057] In formula (6), R 12 represents an alkylene group. Here, examples of the alkylene group include alkylene groups having 1 to 10 carbon atoms, such as an ethylene group and a hexylene group.
[0058] (Fourth aspect) The aerogel according to this embodiment may further contain silica particles in addition to the aerogel component in order to further increase toughness and achieve even better heat insulation and flexibility. An aerogel containing the aerogel component and silica particles can also be called an aerogel composite. The aerogel composite is a composite of the aerogel component and silica particles, but it still has a cluster structure characteristic of aerogel and is considered to have a three-dimensional fine porous structure.
[0059] The aerogel containing the aerogel component and silica particles can be said to be a dried wet gel, which is a condensate of a sol containing at least one selected from the group consisting of silicon compounds having hydrolyzable functional groups or condensable functional groups and hydrolysis products of silicon compounds having hydrolyzable functional groups, and silica particles. Therefore, the descriptions of the first to third aspects can also be applied mutatis mutandis to the aerogel according to this embodiment.
[0060] The silica particles can be used without any particular limitation, and examples thereof include amorphous silica particles. Examples of amorphous silica particles include fused silica particles, fumed silica particles, and colloidal silica particles. Among these, colloidal silica particles have high monodispersity and are easy to suppress aggregation in the sol. The silica particles may also be silica particles having a hollow structure, a porous structure, or the like.
[0061] The shape of the silica particles is not particularly limited, and examples include spherical, cocoon-shaped, and association-type silica particles. Among these, the use of spherical silica particles facilitates the suppression of aggregation in the sol. The average primary particle diameter of the silica particles may be 1 nm or more, 5 nm or more, or even 20 nm or more, from the viewpoint of easily imparting appropriate strength and flexibility to the aerogel and easily obtaining an aerogel with excellent shrinkage resistance during drying. The average primary particle diameter of the silica particles may be 500 nm or less, 300 nm or less, or 100 nm or less, from the viewpoint of easily suppressing the solid-state thermal conductivity of the silica particles and easily obtaining an aerogel with excellent heat insulating properties. From these viewpoints, the average primary particle diameter of the silica particles may be 1 to 500 nm, 5 to 300 nm, or 20 to 100 nm.
[0062] In this embodiment, the average particle size of the aerogel components and the average primary particle size of the silica particles can be obtained by directly observing the aerogel using a scanning electron microscope (hereinafter abbreviated as "SEM"). The "diameter" here refers to the diameter of a particle exposed on the cross section of the aerogel when the cross section is considered to be a circle. Furthermore, the "diameter when the cross section is considered to be a circle" refers to the diameter of a perfect circle when the area of the cross section is replaced with a perfect circle of the same area. The average particle size is calculated by determining the diameter of circles for 100 particles and averaging them.
[0063] The average particle size of silica particles can also be measured from the raw material. For example, the biaxial average primary particle size is calculated as follows from the results of observing 20 random particles using an SEM. Taking colloidal silica particles, which are typically dispersed in water with a solids concentration of about 5 to 40% by mass, as an example, a wafer with patterned wiring is cut into 2 cm square chips, which are immersed in a dispersion of colloidal silica particles for about 30 seconds, then rinsed with pure water for about 30 seconds and dried with nitrogen blowing. The chips are then placed on a sample stage for SEM observation, and an accelerating voltage of 10 kV is applied, and the silica particles are observed at a magnification of 100,000 times, and an image is taken. From the obtained image, 20 silica particles are randomly selected, and the average particle size of these particles is taken as the average particle size.
[0064] The number of silanol groups per 1 g of silica particles is set to 10 × 10 from the viewpoint of easily obtaining an aerogel with excellent shrinkage resistance. 18 It may be 50×10 18 It may be 100×10 18 The number of silanol groups per 1 g of silica particles may be 1000×10 18 It may be 800 × 10 18 It may be 700 × 10 18 From these viewpoints, the number of silanol groups per gram of silica particles may be 10 × 10 18 ~1000×10 18 50 x 10 pieces / g 18 ~800×10 18 It may be 100 x 10 pieces / g. 18 ~700×10 18 It may be pieces / g.
[0065] The content of the polysiloxane compounds contained in the sol (the sum of the content of the polysiloxane compound having a hydrolyzable functional group or a condensable functional group and the content of the hydrolysis product of the polysiloxane compound having a hydrolyzable functional group) may be 5 parts by mass or more, or 10 parts by mass or more, relative to 100 parts by mass of the total amount of sol, from the viewpoint of more easily achieving good reactivity. The content of the polysiloxane compounds contained in the sol may be 50 parts by mass or less, or 30 parts by mass or less, relative to 100 parts by mass of the total amount of sol, from the viewpoint of more easily achieving good compatibility. From these viewpoints, the content of the polysiloxane compounds contained in the sol may be 5 to 50 parts by mass or 10 to 30 parts by mass, relative to 100 parts by mass of the total amount of sol.
[0066] When the sol contains a silicon compound (excluding polysiloxane compounds), the silicon compound group (the content of the silicon compound having a hydrolyzable functional group or a condensable functional group and the content of the hydrolysis product of the silicon compound having a hydrolyzable functional group) may be 5 parts by mass or more, 7 parts by mass or more, or 10 parts by mass or more relative to 100 parts by mass of the total amount of the sol, from the viewpoint of further facilitating obtaining good reactivity. The content of the silicon compound group contained in the sol may be 50 parts by mass or less, 40 parts by mass or less, or 30 parts by mass or less relative to 100 parts by mass of the total amount of the sol, from the viewpoint of further facilitating obtaining good compatibility.
[0067] When the sol contains both a polysiloxane compound group and a silicon compound group, the ratio of the content of the polysiloxane compound group to the content of the silicon compound group may be 1:0.5 or more, 1:0.7 or more, or 1:1 or more, from the viewpoint of more easily achieving good compatibility. The ratio of the content of the polysiloxane compound group to the content of the silicon compound group may be 1:4 or less, 1:3 or less, or 1:2 or less, from the viewpoint of more easily suppressing gel shrinkage. From these viewpoints, the ratio of the content of the polysiloxane compound group to the content of the silicon compound group may be 1:0.5 to 1:4, 1:0.7 to 1:3, or 1:1 to 1:2.
[0068] When silica particles are contained in the sol, the content of the silica particles may be 1 part by mass or more, 2 parts by mass or more, or 4 parts by mass or more relative to 100 parts by mass of the total sol, from the viewpoint of easily imparting appropriate strength to the aerogel and easily obtaining an aerogel with excellent shrinkage resistance upon drying. The content of the silica particles may be 20 parts by mass or less, 17 parts by mass or less, or 15 parts by mass or less relative to 100 parts by mass of the total sol, from the viewpoint of easily suppressing the solid-state thermal conductivity of the silica particles and easily obtaining an aerogel with excellent heat insulation. From these viewpoints, the content of the silica particles may be 1 to 20 parts by mass, 2 to 17 parts by mass, or 4 to 15 parts by mass relative to 100 parts by mass of the total sol.
[0069] <Aerogel particles> The aerogel particles in this embodiment can be obtained, for example, by pulverizing a bulk aerogel as described below.
[0070] The average particle size D50 (also referred to as the average diameter) of the aerogel particles can be 0.1 to 1000 μm, but may also be 0.5 to 700 μm, 1 to 500 μm, 3 to 100 μm, or 5 to 50 μm. When the average particle size D50 of the aerogel particles is large, aerogel particles with excellent dispersibility, handleability, etc. are easily obtained. On the other hand, when the average particle size D50 is small, aerogel particles with excellent dispersibility are easily obtained. The average particle size of the aerogel particles can be appropriately adjusted by the pulverization method and pulverization conditions, sieving, classification method, etc.
[0071] The average particle diameter D50 of aerogel particles can be measured by laser diffraction / scattering. For example, aerogel particles are added to a solvent (ethanol) so that the content is 0.05 to 5% by mass, and the aerogel particles are dispersed by vibrating with a 50W ultrasonic homogenizer for 15 to 30 minutes. Approximately 10 mL of the dispersion is then poured into a laser diffraction / scattering particle size distribution analyzer, and the particle size is measured at 25°C with a refractive index of 1.3 and an absorption of 0. The particle size at 50% of the cumulative value (volume basis) in this particle size distribution is taken as the average particle diameter D50. A Microtrac MT3000 (manufactured by Nikkiso Co., Ltd.) can be used as the measuring device.
[0072] Commercially available aerogel particles can also be used, such as ENOVA MT1100 (manufactured by CABOT) and AeroVa (manufactured by JIOS AEROGEL CORPORATION).
[0073] In this embodiment, the amount of aerogel particles is preferably such that the total content of aerogel particles and aggregates in the coating liquid is 70% by volume or more, more preferably 72% by volume or more, and even more preferably 74% by volume or more, based on the total volume of the solids. The amount of aerogel particles may be such that the total content of aerogel particles and aggregates in the coating liquid is, for example, 99% by volume or less, 98% by volume or less, or 97% by volume or less, based on the total volume of the solids.
[0074] <Method of manufacturing aerogel particles> The method for producing the aerogel particles is not particularly limited, but they can be produced, for example, by the following method.
[0075] The aerogel particles of this embodiment can be produced by a production method that mainly includes a sol production step, a wet gel production step in which the sol obtained in the sol production step is gelled and then aged to obtain a wet gel, a washing and solvent substitution step in which the wet gel obtained in the wet gel production step is washed and (if necessary) solvent-substituted, a drying step in which the washed and solvent-substituted wet gel is dried, and a crushing step in which the aerogel obtained by drying is crushed.
[0076] Alternatively, the composition may be produced by a production method mainly including a sol production process, a wet gel production process, a wet gel crushing process for crushing the wet gel obtained in the wet gel production process, a washing and solvent substitution process, and a drying process.
[0077] The size of the obtained aerogel particles can be further uniformed by sieving, classification, etc. Uniform particle size can improve dispersibility. The term "sol" refers to the state before the gelation reaction occurs, and in this embodiment, refers to the state in which the silicon compound and, optionally, silica particles are dissolved or dispersed in a solvent. The term "wet gel" refers to a gel solid in a wet state that contains a liquid medium but does not have fluidity.
[0078] (Sol generation process) The sol formation process is a process in which a silicon compound and, optionally, silica particles (or a solvent containing silica particles) are mixed together to undergo a hydrolysis reaction, followed by the formation of a sol. In this process, an acid catalyst may be added to the solvent to promote the hydrolysis reaction. Furthermore, as disclosed in Japanese Patent No. 5250900, surfactants, thermally hydrolyzable compounds, etc. may also be added to the solvent. Furthermore, components such as carbon graphite, aluminum compounds, magnesium compounds, silver compounds, and titanium compounds may also be added to the solvent for the purpose of suppressing heat radiation, etc.
[0079] As the solvent, for example, water or a mixture of water and alcohol can be used. Examples of alcohol include methanol, ethanol, n-propanol, 2-propanol, n-butanol, 2-butanol, and t-butanol. Among these, in order to reduce the interfacial tension with the gel wall, alcohols with low surface tension and low boiling points include methanol, ethanol, and 2-propanol. These may be used alone or in combination of two or more.
[0080] For example, when alcohol is used as the solvent, the amount of alcohol can be 4 to 8 moles per mole of the total amount of the silicon compounds and polysiloxane compounds, but may also be 4 to 6.5, or 4.5 to 6 moles. By using an alcohol amount of 4 moles or more, good compatibility can be more easily achieved, and by using an alcohol amount of 8 moles or less, shrinkage of the gel can be more easily suppressed.
[0081] Examples of acid catalysts include inorganic acids such as hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, hypophosphorous acid, bromic acid, chloric acid, chlorous acid, and hypochlorous acid; acidic phosphates such as aluminum acid phosphate, magnesium acid phosphate, and zinc acid phosphate; and organic carboxylic acids such as acetic acid, formic acid, propionic acid, oxalic acid, malonic acid, succinic acid, citric acid, malic acid, adipic acid, and azelaic acid. Among these, organic carboxylic acids are preferred as acid catalysts that further improve the water resistance of the resulting aerogel. Examples of such organic carboxylic acids include acetic acid, but they may also include formic acid, propionic acid, oxalic acid, and malonic acid. These may be used alone or in combination of two or more.
[0082] By using an acid catalyst, the hydrolysis reaction of the silicon compound can be accelerated, and the sol can be obtained in a shorter time.
[0083] The amount of the acid catalyst added can be 0.001 to 0.1 part by mass per 100 parts by mass of the total amount of the polysiloxane compounds and the silicon compounds.
[0084] The surfactant may be a nonionic surfactant, an ionic surfactant, etc. These may be used alone or in combination of two or more.
[0085] Examples of nonionic surfactants that can be used include compounds containing a hydrophilic portion such as polyoxyethylene and a hydrophobic portion mainly composed of an alkyl group, and compounds containing a hydrophilic portion such as polyoxypropylene. Examples of compounds containing a hydrophilic portion such as polyoxyethylene and a hydrophobic portion mainly composed of an alkyl group include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, and polyoxyethylene alkyl ether. Examples of compounds containing a hydrophilic portion such as polyoxypropylene include polyoxypropylene alkyl ether and block copolymers of polyoxyethylene and polyoxypropylene.
[0086] Examples of ionic surfactants include cationic surfactants, anionic surfactants, and amphoteric surfactants. Examples of cationic surfactants include cetyltrimethylammonium bromide and cetyltrimethylammonium chloride, and examples of anionic surfactants include sodium dodecylsulfonate. Examples of amphoteric surfactants include amino acid surfactants, betaine surfactants, and amine oxide surfactants. Examples of amino acid surfactants include acyl glutamic acid. Examples of betaine surfactants include lauryl dimethyl amino acetate betaine and stearyl dimethyl amino acetate betaine. Examples of amine oxide surfactants include lauryl dimethyl amine oxide.
[0087] These surfactants are thought to act to reduce the difference in chemical affinity between the solvent in the reaction system and the growing siloxane polymer, thereby suppressing phase separation in the wet gel formation process described below.
[0088] The amount of surfactant added will depend on the type of surfactant or the type and amount of silicon compound, but can be, for example, 1 to 100 parts by mass per 100 parts by mass of the total amount of polysiloxane compounds and silicon compounds, or 5 to 60 parts by mass.
[0089] The thermally hydrolyzable compound is thought to generate a base catalyst by thermal hydrolysis, making the reaction solution basic and accelerating the sol-gel reaction in the wet gel formation step described below. Therefore, the thermally hydrolyzable compound is not particularly limited as long as it is a compound that can make the reaction solution basic after hydrolysis, and examples thereof include urea; acid amides such as formamide, N-methylformamide, N,N-dimethylformamide, acetamide, N-methylacetamide, and N,N-dimethylacetamide; and cyclic nitrogen compounds such as hexamethylenetetramine. Among these, urea is particularly likely to achieve the above-mentioned accelerating effect.
[0090] The amount of the thermally hydrolyzable compound added is not particularly limited, as long as it is an amount that can sufficiently promote the sol-gel reaction in the wet gel formation step described below. For example, when urea is used as the thermally hydrolyzable compound, the amount added can be 1 to 200 parts by mass per 100 parts by mass of the total amount of the polysiloxane compounds and the silicon compounds. The amount added may also be 2 to 150 parts by mass. By adding an amount of 1 part by mass or more, good reactivity can be more easily achieved, and by adding an amount of 200 parts by mass or less, crystal precipitation and a decrease in gel density can be more easily suppressed.
[0091] The hydrolysis in the sol production step depends on the types and amounts of the silicon compound, silica particles, acid catalyst, surfactant, etc. in the mixed solution, but may be carried out, for example, at a temperature of 20 to 60° C. for 10 minutes to 24 hours, or at a temperature of 50 to 60° C. for 5 minutes to 8 hours. This ensures that the hydrolyzable functional groups in the silicon compound are sufficiently hydrolyzed, and the hydrolyzed product of the silicon compound can be obtained more reliably.
[0092] However, when a thermally hydrolyzable compound is added to the solvent, the temperature environment in the sol formation step may be adjusted to a temperature that suppresses hydrolysis of the thermally hydrolyzable compound and suppresses gelation of the sol. The temperature at this time may be any temperature as long as it can suppress hydrolysis of the thermally hydrolyzable compound. For example, when urea is used as the thermally hydrolyzable compound, the temperature environment in the sol formation step may be 0 to 40°C, but may also be 10 to 30°C.
[0093] (Wet gel production process) The wet gel forming step is a step of gelling the sol obtained in the sol forming step and then aging the gel to obtain a wet gel. In this step, a base catalyst can be used to promote gelation.
[0094] Examples of the base catalyst include carbonates such as calcium carbonate, potassium carbonate, sodium carbonate, barium carbonate, magnesium carbonate, lithium carbonate, ammonium carbonate, copper (II) carbonate, iron (II) carbonate, and silver (I) carbonate; hydrogen carbonates such as calcium hydrogen carbonate, potassium hydrogen carbonate, sodium hydrogen carbonate, and ammonium hydrogen carbonate; alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide; ammonium compounds such as ammonium hydroxide, ammonium fluoride, ammonium chloride, and ammonium bromide; basic sodium phosphates such as sodium metaphosphate, sodium pyrophosphate, and sodium polyphosphate; allylamine, diallylamine, triallylamine, isopropylamine, diisopropylamine, ethylamine, diethylamine, Examples of suitable base catalysts include aliphatic amines such as ethanol, triethylamine, 2-ethylhexylamine, 3-ethoxypropylamine, diisobutylamine, 3-(diethylamino)propylamine, di-2-ethylhexylamine, 3-(dibutylamino)propylamine, tetramethylethylenediamine, t-butylamine, sec-butylamine, propylamine, 3-(methylamino)propylamine, 3-(dimethylamino)propylamine, 3-methoxyamine, dimethylethanolamine, methyldiethanolamine, diethanolamine, and triethanolamine; and nitrogen-containing heterocyclic compounds such as morpholine, N-methylmorpholine, 2-methylmorpholine, piperazine and its derivatives, piperidine and its derivatives, and imidazole and its derivatives. Among these, ammonium hydroxide (aqueous ammonia) is highly volatile and unlikely to remain in the aerogel particles after drying, thereby preventing deterioration of water resistance and being economical. The above base catalysts may be used alone or in combination of two or more.
[0095] The use of a base catalyst can promote the dehydration condensation reaction or dealcoholization condensation reaction of the silicon compound and silica particles in the sol, allowing the sol to gel in a shorter time. This also allows a wet gel with higher strength (rigidity) to be obtained. In particular, since ammonia is highly volatile and does not easily remain in the aerogel particles, the use of ammonia as a base catalyst allows the production of aerogel particles with better water resistance.
[0096] The amount of base catalyst added can be 0.5 to 5 parts by mass, or alternatively 1 to 4 parts by mass, per 100 parts by mass of the total amount of polysiloxane compounds and silicon compounds. By using an amount of 0.5 parts by mass or more, gelation can be carried out in a shorter time, and by using an amount of 5 parts by mass or less, deterioration in water resistance can be further suppressed.
[0097] The gelation of the sol in the wet gel formation step may be carried out in a sealed container to prevent the solvent and base catalyst from volatilizing. The gelation temperature can be set to 30 to 90°C, but may also be set to 40 to 80°C. By setting the gelation temperature to 30°C or higher, gelation can be carried out in a shorter time, and a wet gel with higher strength (rigidity) can be obtained. Furthermore, by setting the gelation temperature to 90°C or lower, it is easier to suppress the volatilization of the solvent (especially alcohol), so gelation can be carried out while suppressing volumetric shrinkage.
[0098] The aging in the wet gel formation step may be carried out in a sealed container to prevent the solvent and base catalyst from volatilizing. The aging strengthens the bonds between the components that make up the wet gel, resulting in a wet gel with sufficient strength (rigidity) to suppress shrinkage during drying. The aging temperature can be 30 to 90°C, but may also be 40 to 80°C. By setting the aging temperature at 30°C or higher, a wet gel with higher strength (rigidity) can be obtained, and by setting the aging temperature at 90°C or lower, volatilization of the solvent (especially alcohol) can be easily suppressed, allowing gelation while suppressing volumetric shrinkage.
[0099] Since it is often difficult to determine the time when the gelation of the sol is completed, the gelation of the sol and the subsequent aging may be carried out in a continuous series of operations.
[0100] The gelation time and aging time can be appropriately set depending on the gelation temperature and aging temperature. When silica particles are contained in the sol, the gelation time can be particularly shortened compared to when silica particles are not contained. This is presumably because the silanol groups or reactive groups of the silicon compound in the sol form hydrogen bonds or chemical bonds with the silanol groups of the silica particles. The gelation time can be 10 to 120 minutes, but may also be 20 to 90 minutes. A gelation time of 10 minutes or more makes it easier to obtain a homogeneous wet gel, while a gelation time of 120 minutes or less simplifies the washing and solvent substitution process to the drying process described below. The total time for the gelation and aging process as a whole can be 4 to 480 hours, but may also be 6 to 120 hours. A gelation time of 4 hours or more makes it possible to obtain a wet gel with higher strength (rigidity), and a gelation time of 480 hours or less makes it easier to maintain the aging effect.
[0101] To decrease the density of the resulting aerogel particles or increase the average pore size, the gelation temperature and aging temperature may be increased within the above ranges, or the total time of the gelation time and aging time may be increased within the above ranges. Alternatively, to increase the density of the resulting aerogel particles or decrease the average pore size, the gelation temperature and aging temperature may be decreased within the above ranges, or the total time of the gelation time and aging time may be decreased within the above ranges.
[0102] (Wet gel crushing process) When the wet gel crushing step is performed, the wet gel obtained in the wet gel production step is crushed. Crushing can be performed, for example, by placing the wet gel in a Henshall mixer, or by performing the wet gel production step in a mixer and operating the mixer under appropriate conditions (rotation speed and time). Alternatively, more simply, the wet gel can be placed in a sealable container, or by performing the wet gel production step in a sealable container and shaking for an appropriate period of time using a shaking device such as a shaker. If necessary, the particle size of the wet gel can also be adjusted using a jet mill, roller mill, bead mill, or the like.
[0103] (Washing and solvent replacement process) The washing and solvent substitution process includes a process of washing the wet gel obtained by the wet gel production process or the wet gel crushing process (washing process) and a process of replacing the washing liquid in the wet gel with a solvent suitable for drying conditions (the drying process described below) (solvent substitution process). The washing and solvent substitution process can be carried out in a form in which only the solvent substitution process is performed without performing the process of washing the wet gel. However, from the viewpoint of reducing impurities such as unreacted substances and by-products in the wet gel and enabling the production of aerogel particles with higher purity, the wet gel may be washed.
[0104] In the washing step, the wet gel obtained in the wet gel generating step or the wet gel crushing step is washed. The washing can be performed repeatedly using, for example, water or an organic solvent. In this case, the washing efficiency can be improved by heating.
[0105] Examples of the organic solvent that can be used include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, acetone, methyl ethyl ketone, 1,2-dimethoxyethane, acetonitrile, hexane, toluene, diethyl ether, chloroform, ethyl acetate, tetrahydrofuran, methylene chloride, N,N-dimethylformamide, dimethyl sulfoxide, acetic acid, formic acid, etc. The above organic solvents may be used alone or in combination of two or more.
[0106] In the solvent substitution step described below, a low surface tension solvent can be used to suppress gel shrinkage due to drying. However, low surface tension solvents generally have extremely low mutual solubility with water. Therefore, when a low surface tension solvent is used in the solvent substitution step, the organic solvent used in the washing step can be a hydrophilic organic solvent that has high mutual solubility with both water and the low surface tension solvent. The hydrophilic organic solvent used in the washing step can serve as a preliminary replacement for the solvent substitution step. Among the above organic solvents, examples of hydrophilic organic solvents include methanol, ethanol, 2-propanol, acetone, and methyl ethyl ketone. Methanol, ethanol, and methyl ethyl ketone are economically advantageous.
[0107] The amount of water or organic solvent used in the washing step can be an amount that can sufficiently replace the solvent in the wet gel and wash it. This amount can be 3 to 10 times the volume of the wet gel. Washing can be repeated until the water content in the wet gel after washing is 10 mass% or less relative to the mass of silica.
[0108] The temperature environment in the washing step can be a temperature equal to or lower than the boiling point of the solvent used for washing. For example, when methanol is used, the temperature can be raised to about 30 to 60°C.
[0109] In the solvent substitution process, the solvent in the washed wet gel is replaced with a predetermined substitution solvent to suppress shrinkage of the aerogel during the drying process. Heating the process can improve substitution efficiency. Specifically, when drying is performed under atmospheric pressure at a temperature below the critical point of the solvent used for drying, low surface tension solvents, as described below, are used as the substitution solvent. On the other hand, when supercritical drying is performed, examples of the substitution solvent include ethanol, methanol, 2-propanol, dichlorodifluoromethane, carbon dioxide, etc., or a mixture of two or more of these.
[0110] An example of a solvent with low surface tension is a solvent with a surface tension of 30 mN / m or less at 20° C. The surface tension may be 25 mN / m or less, or 20 mN / m or less. Examples of low surface tension solvents include aliphatic hydrocarbons such as pentane (15.5), hexane (18.4), heptane (20.2), octane (21.7), 2-methylpentane (17.4), 3-methylpentane (18.1), 2-methylhexane (19.3), cyclopentane (22.6), cyclohexane (25.2), and 1-pentene (16.0); aromatic hydrocarbons such as benzene (28.9), toluene (28.5), m-xylene (28.7), and p-xylene (28.3); and hydrocarbons such as dichloromethane (27.9), chloroform (27.2), carbon tetrachloride (26.9), 1-chloropropane (21.8), and 2-chloropropane (18.1). These include halogenated hydrocarbons; ethers such as ethyl ether (17.1), propyl ether (20.5), isopropyl ether (17.7), butyl ethyl ether (20.8), and 1,2-dimethoxyethane (24.6); ketones such as acetone (23.3), methyl ethyl ketone (24.6), methyl propyl ketone (25.1), and diethyl ketone (25.3); and esters such as methyl acetate (24.8), ethyl acetate (23.8), propyl acetate (24.3), isopropyl acetate (21.2), isobutyl acetate (23.7), and ethyl butyrate (24.6). (The values in parentheses indicate the surface tension at 20°C, in units of mN / m.) Among these, aliphatic hydrocarbons (hexane, heptane, etc.) have low surface tension and are excellent for the working environment. Among these, hydrophilic organic solvents such as acetone, methyl ethyl ketone, and 1,2-dimethoxyethane can be used, and these can also be used as the organic solvent in the washing step. Among these, solvents having a boiling point of 100°C or less at normal pressure may be used, as they are easier to dry in the drying step described below. The above solvents may be used alone or in combination of two or more.
[0111] The amount of solvent used in the solvent substitution step can be an amount that can sufficiently substitute the solvent in the wet gel after washing, and can be 3 to 10 times the volume of the wet gel.
[0112] The temperature environment in the solvent substitution step can be a temperature equal to or lower than the boiling point of the solvent used for substitution, and for example, when heptane is used, the temperature can be raised to about 30 to 60°C.
[0113] It should be noted that when silica particles are contained in the gel, the solvent substitution step is not essential. The presumed mechanism is as follows: The silica particles function as a support for the three-dimensional network skeleton, thereby supporting the skeleton and suppressing gel shrinkage during the drying step. Therefore, it is believed that the gel can be directly subjected to the drying step without replacing the solvent used for washing. In this way, the use of silica particles makes it possible to simplify the washing and solvent substitution steps to the drying step.
[0114] (drying process) In the drying step, the wet gel that has been washed and (if necessary) solvent-substituted as described above is dried. This allows aerogel (aerogel blocks or aerogel particles) to be obtained. That is, the aerogel can be obtained by drying the wet gel produced from the sol.
[0115] The drying method is not particularly limited, and known methods such as atmospheric drying, supercritical drying, or freeze drying can be used. Among these, atmospheric drying or supercritical drying can be used from the viewpoint of ease of producing a low-density aerogel. Furthermore, atmospheric drying can be used from the viewpoint of low-cost production. In this embodiment, atmospheric pressure means 0.1 MPa (atmospheric pressure).
[0116] Aerogels can be obtained by drying a washed and (optionally) solvent-substituted wet gel at atmospheric pressure at a temperature below the critical point of the solvent used for drying. The drying temperature varies depending on the type of substituted solvent (or the solvent used for washing if solvent substitution is not performed), but can be set to 20 to 150°C, taking into consideration that drying at high temperatures can accelerate the evaporation rate of the solvent and cause large cracks in the gel. The drying temperature may also be 60 to 120°C. The drying time varies depending on the volume of the wet gel and the drying temperature, but can be set to 4 to 120 hours. Accelerating drying by applying a pressure below the critical point, as long as it does not impair productivity, is also considered to be atmospheric pressure drying.
[0117] The aerogel can also be obtained by subjecting a wet gel that has been washed and (if necessary) solvent-substituted to supercritical drying, which can be carried out by a known method. Examples of supercritical drying methods include removing the solvent at a temperature and pressure equal to or higher than the critical point of the solvent contained in the wet gel, or immersing the wet gel in liquefied carbon dioxide at, for example, 20 to 25°C and about 5 to 20 MPa to replace all or part of the solvent contained in the wet gel with carbon dioxide having a lower critical point than the solvent, and then removing the carbon dioxide alone or a mixture of carbon dioxide and the solvent.
[0118] The aerogel obtained by such atmospheric drying or supercritical drying may be further dried at atmospheric pressure at 105 to 200°C for about 0.5 to 2 hours. This makes it easier to obtain an aerogel with low density and small pores. The additional drying may be performed at atmospheric pressure at 150 to 200°C.
[0119] (Crushing process) If the wet gel crushing step is not performed, the aerogel (aerogel block) obtained by drying can be crushed to obtain aerogel particles. For example, this can be done by placing the aerogel in a jet mill, roller mill, bead mill, hammer mill, or the like and operating it at an appropriate rotation speed for an appropriate time.
[0120] <Water-soluble polymer> In this embodiment, the water-soluble polymer may have a hydrophobic group and be water-soluble.
[0121] Examples of the hydrophobic group include an alkyl group (preferably a long-chain alkyl group having 6 to 26 carbon atoms), an ester group, an alkoxy group, a halogen atom, etc. Of these, the hydrophobic group is preferably an alkyl group, more preferably a long-chain alkyl group having 8 to 26 carbon atoms, even more preferably a long-chain alkyl group having 10 to 26 carbon atoms, still more preferably a long-chain alkyl group having 12 to 26 carbon atoms, and may be a long-chain alkyl group having 15 to 26 carbon atoms.
[0122] Examples of water-soluble polymers include modified carboxyl vinyl polymers, modified polyether urethane, cellulose-based resins, polyethylene oxide, polyvinyl alcohol, polyacrylates, polyvinylpyrrolidone, dextrin-based resins, chitin-based resins, and chitosan-based resins.
[0123] As the water-soluble polymer, a cellulose-based resin can be suitably used, such as methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and modified products thereof that have been further modified (e.g., hydrophobized).
[0124] The cellulose-based resin is preferably a cellulose-based resin having an alkyl group, and more preferably a cellulose-based resin having a long-chain alkyl group of 6 to 26 carbon atoms. With such a cellulose-based resin, the effects of the present invention are more pronounced. The number of carbon atoms in the long-chain alkyl group is preferably 8 to 26, more preferably 10 to 26, even more preferably 12 to 26, and even more preferably 15 to 26.
[0125] The cellulose-based resin is preferably, for example, a cellulose-based resin having a structural unit represented by the following formula (A-1).
[0126] [ka]
[0127] In formula (A-1), R A represents a hydrogen atom, an alkyl group, a hydroxyalkyl group, -R A1 -OR A2 A group represented by (R A1 represents an alkanediyl group or a hydroxyalkanediyl group, and R A2 represents an alkyl group.) Three R A may be the same or different from each other, provided that three R A At least one of the groups is an alkyl group or -R A1 -OR A2 It is a group represented by the following formula:
[0128] In formula (A-1), R A The alkyl group in R is preferably an alkyl group having 1 to 26 carbon atoms. A The alkyl group in the formula (I) is more preferably a short-chain alkyl group having 1 to 3 carbon atoms, or a long-chain alkyl group having 6 to 26 carbon atoms. The long-chain alkyl group preferably has 8 to 26 carbon atoms, more preferably 10 to 26 carbon atoms, even more preferably 12 to 26 carbon atoms, and even more preferably 15 to 26 carbon atoms.
[0129] In formula (A-1), R AThe hydroxyalkyl group in the formula (I) is preferably a hydroxyalkyl group having 1 to 26 carbon atoms, more preferably a hydroxyalkyl group having 1 to 10 carbon atoms, and even more preferably a hydroxyalkyl group having 1 to 5 carbon atoms.
[0130] In formula (A-1), R A1 The alkanediyl group in R is preferably an alkanediyl group having 1 to 26 carbon atoms, more preferably an alkanediyl group having 1 to 10 carbon atoms, and even more preferably an alkanediyl group having 1 to 5 carbon atoms. A1 The hydroxyalkanediyl group in the formula (I) is preferably a hydroxyalkanediyl group having 1 to 26 carbon atoms, more preferably a hydroxyalkanediyl group having 1 to 10 carbon atoms, and even more preferably a hydroxyalkanediyl group having 1 to 5 carbon atoms.
[0131] In formula (A-1), R A2 is preferably an alkyl group having 1 to 26 carbon atoms. A2 The alkyl group in is more preferably a short-chain alkyl group having 1 to 3 carbon atoms or a long-chain alkyl group having 6 to 26 carbon atoms, and is even more preferably a long-chain alkyl group. The number of carbon atoms in the long-chain alkyl group is preferably 8 to 26, more preferably 10 to 26, even more preferably 12 to 26, and even more preferably 15 to 26.
[0132] In formula (A-1), three R A At least one of the R A At least one of them is -R A1 -OR A2 and R A2 is preferably a long chain alkyl group.
[0133] In the cellulose-based resin, the content of long-chain alkyl groups having 6 to 26 carbon atoms is preferably 0.01 to 5 mass %, more preferably 0.01 to 3 mass %, based on the total amount of the cellulose-based resin.
[0134] In this embodiment, the content of the water-soluble polymer in the coating liquid may be, for example, 0.01% by volume or more, preferably 0.1% by volume or more, and more preferably 0.3% by volume or more, based on the total volume of the solids in the coating liquid. The content of the water-soluble polymer may be, for example, 10% by volume or less, preferably 5% by volume or less, and more preferably 3% by volume or less, based on the total volume of the solids in the coating liquid.
[0135] <Liquid medium> The liquid medium is preferably an aqueous solvent containing water. The aqueous solvent may contain an organic solvent in addition to water. The organic solvent may be any organic solvent as long as it is compatible with water, and examples thereof include alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, and propylene glycol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and methyl ethyl ketone; carboxylic acids such as acetic acid and propionic acid; and nitrogen-containing compounds such as acetonitrile, dimethylformamide, and triethylamine.
[0136] In this embodiment, the content of the liquid medium in the coating liquid is not particularly limited and may be changed appropriately depending on the desired viscosity of the coating liquid, etc. For example, the content of the liquid medium may be an amount that causes the solids concentration of the coating liquid to fall within a suitable range described below.
[0137] The solid content of the coating liquid may be, for example, 10% by mass or more, preferably 15% by mass or more, and more preferably 20% by mass or more, and may be, for example, 70% by mass or less, preferably 60% by mass or less, and more preferably 50% by mass or less.
[0138] <Other ingredients> In this embodiment, the coating liquid may further contain components other than the aerogel particles, the water-soluble polymer, and the liquid medium.
[0139] The coating liquid according to the present embodiment may further contain, for example, a binder resin. Examples of binder resins include epoxy resins, silicone resins, phenolic resins, urea resins, melamine resins, polyurethane resins, polyethylene resins, polypropylene resins, polystyrene resins, polyester resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, polyamide resins, polyimide resins, and polyvinyl resins. Among these, silicone resins, acrylic resins, phenolic resins, and polyester resins are preferably used from the viewpoints of heat resistance and toughness.
[0140] In this embodiment, when the coating liquid contains a binder resin, the content of the binder resin in the coating liquid may be, for example, 30% by volume or less, preferably 28% by volume or less, and more preferably 25% by volume or less, based on the total volume of the solids. Also, the content of the binder resin in the coating liquid may be, for example, 0.1% by volume or more, or 1% by volume or more, based on the total volume of the solids.
[0141] The composite material according to this embodiment may further contain other components, such as a thickener, a fibrous substance, a pigment, and a leveling agent, in addition to the above components.
[0142] Examples of thickeners include fine particles of fumed silica, clay minerals, and the like.
[0143] The fibrous material can exhibit anchoring properties between aerogel particles, further improving the strength of the coating film formed by the composite material. The fibrous material is not particularly limited, and examples thereof include organic fibers and inorganic fibers. Examples of organic fibers include polyamide fibers, polyimide fibers, polyvinyl alcohol fibers, polyvinylidene chloride fibers, polyvinyl chloride fibers, polyester fibers, polyacrylonitrile fibers, polyethylene fibers, polypropylene fibers, polyurethane fibers, phenolic fibers, polyetherester fibers, polylactic acid fibers, and polycarbonate fibers. Examples of inorganic fibers include glass fibers, carbon fibers, ceramic fibers, and metal fibers.
[0144] <Method of manufacturing coating liquid> In this embodiment, the coating liquid may be produced by a production method including: a preparation step of preparing aerogel particles, a water-soluble polymer, and a liquid medium; and a mixing step of mixing the aerogel particles, water-soluble polymer, and liquid medium prepared in the preparation step to agglomerate the aerogel particles, thereby obtaining a coating liquid containing agglomerates of aerogel particles, the water-soluble polymer, and the liquid medium.
[0145] In the preparation step, components other than the aerogel particles, the water-soluble polymer, and the liquid medium (for example, the components described above under <Other Components>) may be further prepared.
[0146] In the mixing step, the components prepared in the preparation step are mixed so as to aggregate the aerogel particles. The mixing method may be any method that can form aggregates of the aerogel particles, and examples thereof include a method in which the components prepared in the preparation step are stirred and mixed.
[0147] The stirring speed affects the size of the aggregates. The higher the stirring speed, the greater the shear stress applied to the coating liquid, and the smaller the size of the aggregates tends to be. Therefore, from the viewpoint of obtaining aggregates of a suitable size, as described below, it is desirable to prepare the coating liquid at a low stirring speed.
[0148] The viscosity during mixing also affects the size of the aggregates. Even at the same stirring speed, the shear stress applied to the coating liquid varies depending on the viscosity. If the viscosity is high, greater shear stress is applied to the coating liquid, resulting in smaller aggregates. On the other hand, if the viscosity of the coating liquid is low, even at the same stirring speed, the shear stress applied to the coating liquid will be smaller, resulting in larger aggregates. Therefore, by adjusting the stirring speed depending on the viscosity of the coating liquid, it is possible to prepare a coating liquid with the desired aggregate size.
[0149] The size of the aggregates can also be changed by using additives. Additives that have a strong influence on the size of the aggregates include surface conditioners, surfactants, dispersants, emulsion resins, etc.
[0150] Surface modifiers and surfactants reduce the surface energy between the aerogel particles and the solution. The lower the surface energy, the weaker the force that tries to reduce the interface, and the smaller the size of the aggregates tends to be. Therefore, the addition of surface modifiers and surfactants reduces the surface energy and reduces the size of the aggregates.
[0151] Dispersants adhere to the particle surfaces and inhibit the particles from approaching each other through electrostatic or steric repulsion. Since dispersants adhere to the surfaces of aerogel particles and inhibit the particles from approaching each other, the addition of a dispersant reduces the size of the aerogel particles.
[0152] Emulsion resin is a resin dispersed in water mainly by a dispersant. Such emulsion resin is adsorbed onto the surface of aerogel particles, and the accompanying dispersant prevents the aerogel particles from approaching each other. In other words, the addition of emulsion resin reduces the size of the agglomerates.
[0153] The amount of liquid medium used during mixing also affects the size of the aggregates. Even if the composition of the coating liquid ultimately produced is the same, the size of the aggregates differs between (i) a method in which the entire amount of liquid medium is added from the beginning of mixing and (ii) a method in which a small amount of liquid medium is mixed at the beginning of mixing and then the liquid medium is added. Compared to method (i), method (ii) results in a higher initial viscosity of the coating liquid, and if the above-mentioned additives are added, their concentration also increases. For this reason, method (ii) tends to produce smaller aggregates than method (i). By using these methods appropriately according to conditions such as the coating liquid composition and the mixing device (stirring device), aggregates of the desired size can be formed.
[0154] The larger the size of the agglomerates, the smaller the contact interface between the aerogel and the resin component, and the more easily the penetration of the resin component into the pores of the aerogel is suppressed. From this viewpoint, in this embodiment, it is preferable that agglomerates with a diameter of 20 μm or more are formed, more preferably that agglomerates with a diameter of 40 μm or more are formed, and even more preferably that agglomerates with a diameter of 50 μm or more are formed. On the other hand, from the viewpoint of avoiding a decrease in film strength due to the continuation of relatively fragile aerogel, the diameter of the agglomerates is preferably 400 μm or less, and more preferably that the diameter is 300 μm or less.
[0155] In this embodiment, the average diameter of the aggregates is preferably at least two times, more preferably at least four times, and even more preferably at least eight times the average diameter of the aerogel particles prepared in the preparation step. This reduces the contact interface between the aerogel and the resin component, making it easier to suppress the penetration of the resin component into the pores of the aerogel. Furthermore, the average diameter of the aggregates is preferably no more than 40 times, more preferably no more than 30 times, and even more preferably no more than 20 times the average diameter of the aerogel particles prepared in the preparation step. This prevents a decrease in film strength due to the formation of a series of relatively fragile aerogel particles, making it easier to obtain a higher film strength.
[0156] In this specification, the average diameter of the aggregates indicates a value measured by the following method. [Method for measuring the average diameter of aggregates in coating liquid] Approximately 20 g of the coating liquid was placed in a 100 mL plastic cup, and water was added in 2 g increments while stirring with a spatula, gradually diluting the mixture. The diluted sample was placed on a glass plate, and a micrograph of the sample was taken using an optical microscope (OLYMPUS, model number: BX51). The obtained micrograph was analyzed using the image editing software ImageJ to determine the diameters of multiple aggregates in the micrograph. The average of the obtained values was taken as the average diameter of the aggregates.
[0157] In this specification, the average diameter of the aerogel particles has the same meaning as the average particle diameter D50 of the aerogel particles described above.
[0158] In this embodiment, when a diluted solution obtained by diluting the coating liquid is observed under an optical microscope, the area occupied by aggregates having a diameter of 20 μm or more (more preferably aggregates having a diameter of 50 μm or more) of the area occupied by aerogel particles and aggregates within the observation field is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, and may even be 100%.
[0159] In this specification, the diluted solution obtained by diluting the coating solution and the method for observing the diluted solution may be the same as the sample prepared in the above-mentioned [Method for measuring the average diameter of aggregates in a coating solution] and the method for observing the sample. Furthermore, the "area within the observation field" is determined by analyzing a micrograph using the image editing software ImageJ.
[0160] <Insulating material manufacturing method> In this embodiment, the thermal insulating material is produced by a production method including: a coating step of applying the coating liquid with a coating means that applies a pressure of 1.5 MPa or less to the coating liquid to obtain a coating film; and a removal step of removing at least a portion of the liquid medium from the coating film to obtain the thermal insulating material. According to this production method, the aerogel particles aggregate in the coating liquid, thereby sufficiently suppressing penetration of the resin into the aerogel pores, and the use of a predetermined coating means makes it possible to form a coating film while suppressing breakup of the aerogel particle aggregates, thereby obtaining a thermal insulating material with high thermal insulating properties and high film-forming properties.
[0161] The object to which the coating liquid is applied is not particularly limited. The object to be coated (e.g., a support) may be peeled off from the insulating material after the insulating material is manufactured, or may be used without being peeled off from the insulating material. The object may be, for example, an object to which the insulating material is applied. The material constituting the object is not particularly limited, and may be, for example, metal, ceramic, glass, resin, composite materials thereof, or the like. The form of the object may be appropriately selected depending on the purpose of use, material, etc., and may be, for example, a block, sheet, powder, fiber, or the like.
[0162] The method for applying the coating liquid is not particularly limited as long as the pressure applied to the coating liquid is 1.5 MPa or less. For example, application methods such as roller application, trowel application, and air spraying are preferred because they tend to reduce the pressure applied to the coating liquid.
[0163] In the removing step, at least a portion of the liquid medium is removed from the coating film to form a heat insulating material made of a composite material containing agglomerates of aerogel particles and a water-soluble resin.
[0164] The method for removing the liquid medium from the coating film is not particularly limited, and examples thereof include heating (for example, 40 to 150° C.), reducing pressure (for example, 10,000 Pa or less), or both.
[0165] The thickness of the heat insulating material is not particularly limited, and may be, for example, 0.01 to 30 mm, or 0.1 to 20 mm.
[0166] The insulation material has pores due to the aerogel particles. The pore volume of the insulation material is set to 0.15 cm3 in order to obtain higher insulation performance. 3 / g or more is preferable, and 0.20 cm 3 / g or more is more preferable, and 0.60cm 3 / g or more is more preferable. There is no particular upper limit to the pore volume of the heat insulating material. The pore volume of the heat insulating material is, for example, 5.0 cm 3 / g or less.
[0167] The thermal conductivity of the heat insulating material is, for example, 0.05 W / (m·K) or less, preferably 0.04 W / (m·K) or less, and more preferably 0.035 W / (m·K) or less. There is no particular lower limit to the thermal conductivity of the heat insulating material. The thermal conductivity of the heat insulating material may be, for example, 0.01 W / (m·K) or more.
[0168] The thermal insulation material produced by the production method of this embodiment has excellent thermal insulation properties, heat resistance, flame retardancy, etc., derived from the aerogel. Therefore, the thermal insulation material can be used as a thermal insulation material in cryogenic containers, the space field, the construction field, the automotive field, the home appliance field, the semiconductor field, industrial equipment, etc. In addition to its use as a thermal insulation material, the thermal insulation material can also be used as a water repellent material, a sound absorbing material, a vibration silencing material, a catalyst carrier material, etc.
[0169] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above embodiments. [Example]
[0170] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0171] (Method of producing coating liquid) A 500 mL separable flask was charged with 6 parts by weight of Sangelose 90L (Daido Chemical Industry Co., Ltd.) as a water-soluble polymer, 46 parts by weight of isopropyl alcohol (Fujifilm Wako Pure Chemical Industries, Ltd., reagent), and 840 parts by weight of hot water. The mixture was stirred at 200 rpm using a mechanical stirrer for 1 minute to obtain a dispersion. Next, while cooling the flask in an ice-water bath, the mixture was stirred at 200 rpm using a mechanical stirrer to dissolve the Sangelose 90L, obtaining a pregel, an aqueous solution of Sangelose 90L. 892 parts by weight of the pregel and 1,000 parts by weight of an acrylic resin emulsion aqueous solution (DIC Corporation, product name: Boncoat DV759-EF) were charged to a planetary mixer (Primix Corporation, 2P-1 model) and stirred at 100 rpm. Next, 100 parts by mass of aerogel particles (manufactured by CABOT, product name: ENOVA MT1100, particle diameter 2-24 μm, average particle size (D50) 10 μm) were added, and the mixture was stirred at 100 rpm to obtain a coating solution. Based on the total volume of solids in the coating solution, the aerogel particle content was 74.7 vol%, the water-soluble polymer content was 0.4 vol%, and the acrylic resin content was 24.9 vol%.
[0172] Example 1 100 parts by weight of the coating solution prepared above and 10 parts by weight of pure water were placed in a plastic cup and stirred at 200 rpm for 5 minutes using a mechanical stirrer to dilute the coating solution. The diluted coating solution was applied to aluminum foil (UACJ Corporation, product name: My Foil Thick Type 50, thickness: 50 μm) using a sand and aggregate roller (Otsuka Brush, sand and aggregate regular roller, coarse, 4 inches) with a load of 500 g to achieve a coating thickness of 2 mm. The coating was then left at room temperature (23°C) for 12 hours to remove the liquid medium and obtain a thermal insulating material. The pressure applied to the coating solution during roller application was 25 kPa, calculated from the roller's contact area and load.
[0173] Example 2 The diluted solution prepared in Example 1 was taken into a multi-use gun (Meiji Kikai, SGA-2) and applied to aluminum foil in the same manner as in Example 1 using a paint nozzle diameter of 5.5 mm and a spray air pressure of 0.06 MPa, and then dried to obtain an insulating material.
[0174] Example 3 The diluted solution prepared in Example 1 was applied to aluminum foil in the same manner as in Example 1 using a pressure tank (Meiji Kikai, P-2A) and a spray gun (Meiji Kikai, F210-P12P) at a liquid supply pressure of 0.3 MPa, and then dried to obtain an insulating material.
[0175] (Comparative Example 1) The diluted solution prepared in Example 1 was placed in a dedicated cup of an airless sprayer (Ultra Max, manufactured by Graco) and applied to aluminum foil at a coating pressure of 3.4 MPa in the same manner as in Example 1, followed by drying to obtain a heat insulating material.
[0176] The examples and comparative examples were evaluated by the following methods, and the results are shown in Table 1.
[0177] <Microscopic observation of coating fluid> Approximately 20 g of the coating solution was placed in a 100 mL plastic cup, and water was added in 2 g increments while stirring with a spatula, gradually diluting the solution while mixing. The diluted sample was placed on a glass plate, and the aerogel particles and their aggregates in the coating solution were observed using an optical microscope (OLYMPUS, model number: BX51), and micrographs were taken. The micrographs were analyzed using the image editing software ImageJ to determine the average diameter of the aerogel particle aggregates.
[0178] <Crack evaluation of insulation materials> An aluminum foil (manufactured by UACJ Corporation, product name: My Foil Thick Type 50, thickness: 50 μm) was attached to an aluminum plate (25 cm × 40 cm × 0.1 cm) serving as a support plate, and a coating solution was applied to a length and width of 200 to 250 mm and a thickness of 2 mm using the method shown in the Examples or Comparative Examples. The coating solution was then left to stand at room temperature of 23°C for 12 hours to remove the liquid medium from the coating solution, yielding a thermal insulating material. The resulting thermal insulating material was evaluated for cracking, with A representing a material with no cracks throughout, B representing a material with partial cracks, and C representing a material with cracks throughout.
[0179] <Evaluation of pore volume of insulation material> A thermal insulating material was prepared using the same method as in the above <Crack evaluation of thermal insulating material>. 100 mg of the prepared thermal insulating material was sampled, and the pore volume was calculated using a high-sensitivity gas adsorption analyzer (Quantachrome, AutoSorb iQ).
[0180] <Evaluation of thermal conductivity of insulation materials> An insulating material was prepared on aluminum foil (manufactured by UACJ Corporation, product name: My Foil Thick Type 50, thickness: 50 μm) using the same method as in <Evaluation of cracking of insulating material>, and then coated twice more to prepare a plate-shaped sample measuring 200 to 250 mm in length and width and 3 mm in thickness. After drying, the aluminum foil was peeled off and the edges were cut off to form a 200 mm in length and width. The thermal conductivity of the obtained insulating material was measured using a thermal conductivity measuring device "HFM-446" (manufactured by NETZSCH, product name) using a steady-state method. Note that this evaluation was performed only on the coating liquids of Example 1 and Comparative Example 1.
[0181] [Table 1]
[0182] As shown in Table 1, in the examples, a high pore volume and high thermal insulation were achieved, and cracking during film formation was also suppressed. On the other hand, in the comparative examples, the pore volume was small and the thermal conductivity was high due to the application method, and cracking occurred throughout the film during formation.
Claims
1. a coating step of mixing aerogel particles, a water-soluble polymer having a hydrophobic group, and a liquid medium so that the aerogel particles are aggregated, and applying the coating liquid obtained by the above-mentioned coating liquid with a coating means having a pressure of 1.5 MPa or less to obtain a coating film; a removing step of removing at least a portion of the liquid medium from the coating film to obtain a thermal insulating material; A method for producing an insulating material, comprising:
2. the coating liquid contains aggregates of the aerogel particles, 2. The method of claim 1, wherein the average diameter of the aggregates is 2 to 40 times the average diameter of the aerogel particles.
3. 3. The manufacturing method according to claim 1, wherein, when a diluted solution obtained by diluting the coating liquid is observed under an optical microscope, an area occupied by the aerogel particles and agglomerates of the aerogel particles within an observation field of view is 50% or more of an area occupied by the aerogel particles and agglomerates of the aerogel particles.
4. The method according to any one of claims 1 to 3, wherein a total content of the aerogel particles and the aerogel particle aggregates in the coating liquid is 70 volume % or more based on a total volume of solids.
5. The method according to any one of claims 1 to 4, wherein the water-soluble polymer comprises a cellulose-based resin.
6. The pore volume of the insulating material is 0.15 cm 3 The method according to any one of claims 1 to 5, wherein the molecular weight of the polymer is 1 / g or more.
Citation Information
Patent Citations
Oily cosmetic for lip
JP2008031044A
aerogel
JP2012091943A
Heat insulating material and method for producing the same
JP2014035044A
Hair dye
JP2017210446A
Aqueous dispersion of hydrophobic silica aerogel particles, solid composite material, heat insulating material and sound absorbing material
JP2018043927A